All about Nina [videorecording (DVD)] - Vives, Eva; Vives, Eva; Vives, Eva; Winstead, Mary Elizabeth; Common (Musician); Crawford, Chace, 1985- (The Orchard, 2018)
A troubled stand-up comedienne flees to Los Angeles to prepare for a potentially life changing audition.